Comparison of Reactors for Hydrogen Production via Methane Steam Reforming: A Review - Amin, Mustafa; Fatahalrahman, Mohammed (University of Khartoum Engineering Journal, 2025)
Methane Steam Reforming (MSR) remains the dominant technology for hydrogen production due to its high efficiency and economic viability. This paper provides a comparative analysis of different reactors used for MSR, including fixed-bed reactors, fluidized-bed reactors, microreactors, membrane reactors, and sorption-enhanced reactors. Fixed-bed reactors are widely employed in industrial settings for their simplicity and robustness; however, they face limitations in heat transfer and equilibrium-constrained methane conversion. Fluidized-bed reactors address these issues by improving heat and mass transfer, but they introduce complexities related to catalyst attrition and operational control. Microreactors leverage their high surface area-to-volume ratio to achieve excellent heat transfer and reaction kinetics, making them ideal for small-scale and portable applications, albeit with limited throughput for large-scale operations. Sorption-enhanced reactors further enhance hydrogen production by in-situ CO₂ capture, enabling methane conversions of up to 85% and hydrogen purity exceeding 95%, though sorbent regeneration poses technical barriers. Finally, membrane reactors integrate hydrogen separation with the reforming process, shifting equilibrium towards higher methane conversion and hydrogen yield, though the high cost and stability of palladium-based membranes remain challenges. The study highlights the challenges faced by these reactor technologies, including catalyst performance, economic constraints, and scalability issues, while discussing future perspectives such as the integration of renewable energy sources, and advanced catalyst development. Advancements in these areas will be crucial for enhancing the efficiency, cost-effectiveness, and sustainability of MSR processes, paving the way for cleaner and more reliable hydrogen production.